New and little-known species of isopods (Crustacea, Isopoda) from the eastern Mediterranean - Castelló, José (Zootaxa, 2017)
New species of Anthuridae and Cirolanidae (Crustacea, Isopoda) are described from the coasts of Cyprus and Lebanon, Mediterranean. Mesanthura pacoi sp. nov. is the first species of the genus found in the Mediterranean; its pale color, usually without dorsal spots, and the setation of the apical segment of the maxillipedal palp, are unique in this genus. Atarbolana beirutensis sp. nov. differs from the rest of species of this genus due to its uropodal exopod shaped like an elongated spoon, rather than a cylinder. This is the first record of the genus Atarbolana in the Mediterranean. The two species of Cirolana described have flat penes, absent in C. cranchi and C. manorae, the other two species found in this study; C. bitari sp. nov. has a depressed body and articles of antennal flagellum with one tuft of simple setae on the anterodistal angle, while in C. zibrowiusi sp. nov. the body is cylindrical, slightly depressed, and the articles of the antennal flagellum have two tufts of simple setae. In addition, one female specimen of Pseudocerceis, identified as P. cf. seleneides is described; it is the first record of this genus in the Mediterranean.